Guidance for pregnant women monitored in prenatal care by multiprofessional family health teams (Research, Society and Development, 2020)
The present study aimed to identify the guidelines made available to pregnant women on childbirth, breastfeeding and newborn care based on prenatal consultations carried out by professionals from three Family Strategy and Health teams in a Basic Health Unit in the south of Rio Grande do Sul. It is a qualitative, descriptive research carried out with seven pregnant women, in the last trimester of pregnancy, who were undergoing prenatal care in November 2019. Data collection was through semi-structured interviews and the findings treated through the operative proposal of content analysis. The project was approved under opinion number 3,666,875 by a Research Ethics Committee. The interviewees also seek guidance in electronic media, such as the internet and applications. The most discussed topic was about breastfeeding. They also reported a lack of information and hearing about feelings, anxieties, insecurities and fears that still existed and doubts about the delivery, despite being under prenatal care. The pregnant women felt they were receiving qualified attention, but still, in an insufficient way, guidance on childbirth and care for the newborn. Further studies are needed to explore strategies for primary care professionals to invest in different health education devices for pregnant women in prenatal care.